Domain Specificity or Generality: Assessing the Chinese Implicit Theories Scale of Six Fundamental Psychological Attributes - Zhu, Shimin; Zhuang, Yanqiong; Cheung, Sing-Hang (Frontiers in Psychology, 2020)
Implicit theories have been widely studied in different domains; however, it is still debatable whether these theories are domain-specific or domain-general. Using the Implicit Theories Scale (ITS) about six fundamental psychological attributes, i.e., intelligence, personality, cognition, feeling, behavior, and emotion, we examined domain specificity versus generality using a factor analytic approach; in addition, we investigated associations between implicit theories about these domains and related psychological attributes. In four sequential studies, we translated a Chinese version of the ITS (Study 1), tested inter-item correlations within and between subscales (Studies 1–4), and conducted exploratory factor analysis (Studies 2 and 3) and confirmatory factor analysis (Studies 3 and 4). We tested associations between implicit theory domains and coping, resilience, grit, and school performance (Studies 3 and 4). Results showed that the six ITS subscales were independent, while the implicit theories about cognition, feeling, behavior, and emotion shared a common component. The implicit theories of intelligence and personality were independent and did not share a common component. The six domains presented different patterns of association with psychological variables. Overall, our results suggest that implicit theories are both domain-specific and domain-general. Future studies are needed to examine the mechanism underlying the domain specificity and generality of implicit theories.